Corporations vs. Countries. Fostering Governance Sustainability in a Global Environment - Bodislav, Dumitru Alexandru; Dobrea, Cătălin Răzvan; Bran, Florina; Moncea, Mădălina (European Journal of Sustainable Development, 2023)
This research study integrates the results from theoretical and real-world scenarios in the frameworks of corporate governance, state governance, and public administration. Whether it be via the tight examination of the private sector or the public sector, the strategy adopted in this research involved constructing a 360-degree focus on real occurrences that generate the formal and informal processes that keep the globe going. In the first portion of the article, the global mechanism as viewed from the perspective of business and the worldwide mechanism as seen from the standpoint of the economy are both given their own section. Keywords: corporate governance, economic growth, free trade, global accountability